2021
DOI: 10.3390/ijerph19010053
|View full text |Cite
|
Sign up to set email alerts
|

Does Exposure to High Job Demands, Low Decision Authority, or Workplace Violence Mediate the Association between Employment in the Health and Social Care Industry and Register-Based Sickness Absence? A Longitudinal Study of a Swedish Cohort

Abstract: Background: The aim of this paper was to investigate if job demands, decision authority, and workplace violence mediate the association between employment in the health and social care industry and register-based sickness absence. Methods: Participants from the Swedish Longitudinal Occupational Survey of Health who responded to questionnaires in 2006–2016 (n = 3951) were included. Multilevel autoregressive cross-lagged mediation models were fitted to the data. Employment in the health and social care industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…According to our study data, we observed a higher rate of absenteeism occurring in the emergency department due to WPV than in other departments. This result is consistent with the findings in the USA [ 13 ], China [ 19 ], Sweden [ 36 ], and Finland [ 23 ], where HWs who worked in the emergency department were injured due to WPV taking sick leave or quitting their job. This level of absenteeism is alarming in the emergency department, where severe and emergency cases are treated.…”
Section: Discussionsupporting
confidence: 91%
“…According to our study data, we observed a higher rate of absenteeism occurring in the emergency department due to WPV than in other departments. This result is consistent with the findings in the USA [ 13 ], China [ 19 ], Sweden [ 36 ], and Finland [ 23 ], where HWs who worked in the emergency department were injured due to WPV taking sick leave or quitting their job. This level of absenteeism is alarming in the emergency department, where severe and emergency cases are treated.…”
Section: Discussionsupporting
confidence: 91%